Survival and nutritional dependence on home parenteral nutrition: Three decades of experience from a single referral centre. Issue 2 (April 2017) - Dibb, Martyn; Soop, Mattias; Teubner, Antje; Shaffer, Jon; Abraham, Arun; Carlson, Gordon; Lal, Simon
Summary: Background: Home parenteral nutrition (HPN) is the mainstay of treatment for patients with Type 3 intestinal failure (IF), however long term data on mortality and nutritional outcomes are limited. Objectives: To assess the long-term survival and requirements for ongoing HPN in patients receiving treatment at a UK national referral centre for intestinal failure. Methods: Patients with IF who received HPN for more than 3 months at this Intestinal Failure Unit between 1978 and 2011 had their clinical records reviewed. SPSS 20 was utilised to perform Cox regression analysis and generate Kaplan Meier curves, with the aim of identifying factors associated with death and the continued need for HPN. Results: Case notes from 545 patients were reviewed. Overall survival (OS) in patients without malignancy at commencement of IF was 93%, 71%, 59% and 28% at 1, 5, 10 and 20 years after starting treatment. Crohn's disease, mesenteric ischaemia and chronic intestinal pseudo-obstruction were associated with a better OS than scleroderma and radiation enteritis on multivariate analysis. Older age at onset of IF was associated with poor OS, while shorter small bowel length or central line sepsis was not. 15% (25/170) of deaths were due to complications of HPN (central line sepsis = 10, IF-associated liver disease = 15). Continued HPN dependence in survivors was 83%, 63%, 59% and 53% at 1, 5, 10 and 15 years, respectively. Among the 153 patients without malignancy who achieved nutritional independence from HPN, 77 (50.3%) did so after surgical reconstruction of the alimentary tract (HPN duration mean 19 months, range 3–126 months). 76 patients (49.7%) weaned from HPN without undergoing surgical reconstruction. Conclusion: This is the largest reported data set on long-term survival and dependence on HPN and will inform the indications, benefits and risks of treatment in disease specific groups. A significant proportion of patients achieved nutritional autonomy without surgical intervention.